Pengembangan Daya Saing UMKM melalui Pendampingan Pemasaran Digital di Kecamatan Kismantoro, Kabupaten Wonogiri - Purwanta; Anirotun Nisa; Ari Susanti; Defa Rizky Pratama; Lestari; Raisma Nadhifa (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
Kismantoro District, Wonogiri Regency, Central Java is an area that has abundant natural resources. This potential has been utilized by local residents as a means of livelihood, one of which is through Micro, Small and Medium Enterprises (MSMEs) in the form of home industries. The types of MSMEs found in this region are herbal medicine production, tile industry, woven, various kinds of processed snacks, tempeh, bird cages, textiles, and so on. The large potential of MSMEs requires optimization in the field of marketing to maximize economic growth. Therefore, it is necessary to empower MSME actors through training and assistance in the product marketing process. The method in this study consisted of collecting data using observation, interviews, and recording then taking samples with purposive sampling while analyzing data using qualitative description data analysis techniques. Digital marketing training and assistance programs are presented to answer the problems and needs of MSMEs in local villages. Through this program, the existence of MSMEs can be known by the wider community through information on Google Maps and menu catalogs that can be shared on social media. For internal MSMEs, the presentation of information related to cooperation contracts and marketing strategies can be taken into consideration in managing MSME finances. The socialization regarding marketing strategies is expected to increase the understanding of MSME players regarding the steps of the marketing strategy and to be able to implement the steps of the marketing strategy so that products can be marketed more optimally. Through this program, MSMEs are able to implement the knowledge and knowledge gained, utilize social media to improve product marketing and be able to manage product marketing digitally so that products can be marketed more optimally.